From paperwork to pixels: workload and digital governance in Armenian local authorities - Gasparyan, Arman (Frontiers in Political Science, 2024)
This study examines the impact of amalgamation reforms on workload and digital governance within Armenian local authorities, against a backdrop of decentralization and government consolidation. It explores how these reforms affect public servants at different governmental levels and ordinary citizens, highlighting the transition towards e-governance as a mitigatory strategy. The research employed a mixed-method approach, incorporating document analysis, semi-structured interviews with government officials across various levels, and focus group discussions with citizens from amalgamated communities. This comprehensive methodology aimed to assess the shifts in workload distribution and the effectiveness of digital governance tools post-amalgamation. Findings indicate a significant shift in work responsibilities towards local administrators, particularly after community amalgamations, leading to increased workloads. While digital governance tools were introduced to alleviate these pressures, their effectiveness varied. Smaller communities reported satisfaction with service delivery improvements, attributing this to enhanced government support and capacity. However, larger communities faced challenges, including dissatisfaction with service delivery, loss of local identity, and perceived inequities in tax contributions versus benefits received. The study reveals that while amalgamation and digital governance initiatives aim to enhance administrative efficiency and public service delivery, they also present complex challenges. These include managing increased workloads and ensuring equitable service provision across communities. The research contributes to the discourse on local governance reform, emphasizing the need for a balanced approach that considers the implications for democracy, accountability, and citizen engagement in the face of significant structural changes.